2007
DOI: 10.1016/j.bbi.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Protein hormones and immunity

Abstract: A number of observations and discoveries over the past 20 years support the concept of important physiological interactions between the endocrine and immune systems. The best known pathway for transmission of information from the immune system to the neuroendocrine system is humoral in the form of cytokines, although neural transmission via the afferent vagus is well documented also. In the other direction, efferent signals from the nervous system to the immune system are conveyed by both the neuroendocrine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 66 publications
3
119
1
8
Order By: Relevance
“…For example, TNF-α and IL-6 induce IGF-1 resistance in neurons and muscle cells (Kelley 2004;Kelley et al 2007). While the molecular mechanism mediating inflammationneuroendocrine interaction is not known, the activation of the IL-6 modulated JAK-STAT-SOCS pathway may be involved (Bodell et al 2009;Haddad et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TNF-α and IL-6 induce IGF-1 resistance in neurons and muscle cells (Kelley 2004;Kelley et al 2007). While the molecular mechanism mediating inflammationneuroendocrine interaction is not known, the activation of the IL-6 modulated JAK-STAT-SOCS pathway may be involved (Bodell et al 2009;Haddad et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, experience from Snell dwarf mice, which carry defects in GH, prolactin, thyroid hormones and IGF-I production, and from GH-deficient humans, led to the hypothesis that the whole GH/IGF-I axis may be involved (reviewed previously). 11,12 Since then, numerous indications have been found that IGF-I plays a role in the proliferation and differentiation of lymphatic cells and tissues (reviewed previously 1,[12][13][14][15][16][17] ). For instance, in human T-lymphoblast cell lines the stimulatory action of GH on colony formation was attributed to a local production of IGF-I.…”
Section: Discussionmentioning
confidence: 99%
“…With special reference to protein hormones, this idea has been well documented for prolactin (PRL), growth hormone (GH), and insulin-like growth factor-1 (IGF-I). 89 Unfortunately, the effects of these hormones on cancer vaccine-induced immune responses remain unexplored.…”
Section: Hormones and Neuromediatorsmentioning
confidence: 99%